Metode Sederhana Pengolahan Limbah Deterjen Untuk Mengurangi Pencemaran Lingkungan - Jasman, Jasman; Makaminan, Muhammad Ali; Sunati, Nurmila; Layuk, Semuel; Katiandagho, Dismo (POLTEKKES KEMENKES MANADO, 2022)
Disposal of detergent waste into water bodies, both rivers and seas will affect the biota in the water. The effect of laundry detergent waste on tilapia mortality has a significant effect and difference at each concentration. The higher the concentration of detergent waste, the higher the mortality of tilapia. The physiological index of tilapia has a significant effect on the exposure to detergent waste. Detergent wastewater treatment methods are needed as an alternative to solving the problem of wastewater treatment before being discharged into the environment. The purpose of this study is to determine the effectiveness of limestone and coconut shell filter media in reducing the content of detergent, BOD and COD pollutants in wastewater. The research method is a quasi-experimental approach with a pre-test – post-test design approach. The population and sample of this research are wastewater taken from laundry or used laundry in Paal Dua village, Manado city. The results showed a reduction in detergent content from 29.98 mg/l to 0.08 mg/l with a percentage reaching 99.69%. The parameters of BOD and COD decreased by 57.5% and 76.16%, respectively. Based on the results of the T test, there are differences in the average results of measurements before and after processing. Conclusion : Limestone and coconut shell can be used as alternative filter media for detergent wastewater treatment.